Phytoglobin Expression Alters the Na+/K+ Balance and Antioxidant Responses in Soybean Plants Exposed to Na2SO4 - Mohamed S. Youssef (International Journal of Molecular Sciences, 2022)
Soybean (Glycine max) is an economically important crop which is very susceptible to salt stress. Tolerance to Na2SO4 stress was evaluated in soybean plants overexpressing or suppressing the phytoglobin GmPgb1. Salt stress depressed several gas exchange parameters, including the photosynthetic rate, caused leaf damage, and reduced the water content and dry weights. Lower expression of respiratory burst oxidase homologs (RBOHB and D), as well as enhanced antioxidant activity, resulting from GmPgb1 overexpression, limited ROS-induced damage in salt-stressed leaf tissue. The leaves also exhibited higher activities of the H2O2-quenching enzymes, catalase (CAT) and ascorbate peroxidase (APX), as well as enhanced levels of ascorbic acid. Relative to WT and GmPgb1-suppressing plants, overexpression of GmPgb1 attenuated the accumulation of foliar Na+ and exhibited a lower Na+/K+ ratio. These changes were attributed to the induction of the Na+ efflux transporter SALT OVERLY SENSITIVE 1 (SOS1) limiting Na+ intake and transport and the inward rectifying K+ channel POTASSIUM TRANSPORTER 1 (AKT1) required for the maintenance of the Na+/K+ balance.